International Economic Crisis and the Hungarian Pension Reform - András Simonovits (Hungarian Academy of Sciences, Institute of Economics, 2011)
By 2008, the Hungarian pension system has become too generous and the implied contribution rate hindered growth. When the international economic and financial crisis deprived Hungary from normal credits, its government turned to international organizations for help. The most spectacular element of the conditions attached to the bail-out package was the short and long-run reduction of pension benefits. Within months, the Hungarian government eliminated the unsustainable 13th month benefit, reduced health-insurance contribution rates, replaced wage-price indexation with price indexation and worked out a drastic rise in the normal retirement age in the medium-run. The newly elected conservative party has practically closed the second pillar and plans to use up the released capital to reduce the government deficit, debt and finance public expenditures.
Keywords: F34; F44; H12; H55; 330; international economic crisis; Hungary; pension reform; Wirtschaftskrise; International; Wirkungsanalyse; Altersvorsorge; Rentenreform; Ungarn